2015
DOI: 10.1016/j.fusengdes.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Early stage damage of ultrafine-grained tungsten materials exposed to low energy helium ion irradiation

Abstract: BTEM micrographs of the ultrafine-grained tungsten sample irradiated with 30 eV He particles to a fluence of 1x 10 23 m -2 at 600 °C showing (a) several rod-shape nanostructures; (b) high resolution image of a rod-shape nanostructure; (c) region of bubbles in between two rod-shape nanostructures and (d) region of highly dense large bubbles ~ 10 nm below the sample surface. Images in (c) and (d) were taken at under-focus conditions. Graphical Abstract (for review) Abstract Tungsten is considered as a plasma fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In another account [25], a He ion fluence of ∼ 10 24 m -2 on tungsten is shown to lead to a He uptake of ∼ 5 × 10 20 m -2 in the near surface, and according to [26], this level of trapped He in the tungsten surface gives rise to the onset of a dense nanobubble field under examination by TEM. At lower retained He fluence the authors of [26,27] note only platelet formation and dislocation loops; the precursor stages of bubble growth. The low fluence behavior of the fuzz layer thickness data in figure 2, is thus remarkably similar to that associated with the production of a near surface He bubble field found in earlier accounts.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…In another account [25], a He ion fluence of ∼ 10 24 m -2 on tungsten is shown to lead to a He uptake of ∼ 5 × 10 20 m -2 in the near surface, and according to [26], this level of trapped He in the tungsten surface gives rise to the onset of a dense nanobubble field under examination by TEM. At lower retained He fluence the authors of [26,27] note only platelet formation and dislocation loops; the precursor stages of bubble growth. The low fluence behavior of the fuzz layer thickness data in figure 2, is thus remarkably similar to that associated with the production of a near surface He bubble field found in earlier accounts.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Detrimental changes in the mechanical properties such as swelling, hardening and embrittlement 16 can ultimately result in failure 17 . In addition to the microstructural changes caused by freely migrating defects, any energetic particle introduced to the sample (helium for example) can also coalesce and combine with vacancies and voids to form bubbles, which have been shown to exacerbate the unfavorable effects on the irradiated materials 13 , 18 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, experiments have indicated that line dislocations will collect helium preferentially [7,8], but comparisons of dislocation effects under low-energy helium across different tungsten microstructures are lacking. Grain boundaries also sequester plasma-introduced helium differently than the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies (e.g., Refs. [3,7,8,19,20], amongst many others) have well-explored individual aspects of surface morphology changes.…”
Section: Introductionmentioning
confidence: 99%